Sprechprüfungen: Kommentierte Auswahlbibliographie - Matz, Frauke; Rogge, Michael; Rumlich, Dominik (Der Fremdsprachliche Unterricht Englisch)

Bilingualer Sachfachunterricht - Fleckenstein, Johanna; Rumlich, Dominik; Möller, Jens (Englisch unterrichten)

Entwicklung eines Online-Workshops zum „Lernen-Lernen“: Individualisiertes Lernen mit Moodle - Rumlich, Dominik; Hellenbrand, Johannes; Leutner, Detlev (Flexibles Lernen mit digitalen Medien ermöglichen – Strategische Verankerung und Erprobungsfelder guter Praxis an der Universität Duisburg-Essen)

Freiraum zur individuellen Reflexion gemeinsamer Werte - Geierhos, Michaela (Integration und Toleranz)

Changing Uses of the City in Contemporary Black British Novels - Tönnies, Merle; Lienen, Anna (Resistance and the City. Negotiating Urban Identities: Race, Class, Gender)

Visualising Memory Loss and the Politics of Representation in Contemporary Portraiture - Strauß, Sara (Age Matters)

Identity Politics in George Lucas’ Star Wars. by John C. McDowell - Flotmann-Scholz, Christina (Cercles: Revue Pluridisciplinaire du Monde Anglophone)

Rate Your Physician: Findings from a Lithuanian Physician Rating Website - Bäumer, Frederik Simon; Kersting, Joschka; Kuršelis, Vytautas; Geierhos, Michaela (Communications in Computer and Information Science)
Physician review websites are known around the world. Patients review the subjectively experienced quality of medical services supplied to them and publish an overall rating on the Internet, where quantitative grades and qualitative texts come together. On the one hand, these new possibilities reduce the imbalance of power between health care providers and patients, but on the other hand, they can also damage the usually very intimate relationship between health care providers and patients. Review websites must meet these requirements with a high level of responsibility and service quality. In this paper, we look at the situation in Lithuania: Especially, we are interested in the available possibilities of evaluation and interaction, and the quality of a particular review website measured against the available data. We thereby identify quality weaknesses and lay the foundation for future research.
Keywords: Lithuanian physician review websites; Medical service ratings

NLP in OTF Computing: Current Approaches and Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 24th International Conference on Information and Software Technologies (ICIST 2018))
On-The-Fly Computing is the vision of covering software needs of end users by fully-automatic compositions of existing software services. End users will receive so-called service compositions tailored to their very individual needs, based on natural language software descriptions. This everyday language may contain inaccuracies and incompleteness, which are well-known challenges in requirements engineering. In addition to existing approaches that try to automatically identify and correct these deficits, there are also new trends to involve users more in the elaboration and refinement process. In this paper, we present the relevant state of the art in the field of automated detection and compensation of multiple inaccuracies in natural language service descriptions and name open challenges needed to be tackled in NL-based software service composition.
Keywords: Inaccuracy detection; Natural language software requirements

Text Broom: A ML-based Tool to Detect and Highlight Privacy Breaches in Physician Reviews: An Insight into Our Current Work - Bäumer, Frederik Simon; Geierhos, Michaela (European Conference on Data Analysis 2018: Multidisciplinary Facets of Data Science - Book of Abstracts)

Analysing Constructional Change: Linguistic Annotation and Sources of Uncertainty - Merten, Marie-Luis; Seemann, Nina (Proceedings of the 6th International Conference on Technological Ecosystems for Enhancing Multiculturality (TEEM'18))
This paper presents the various sources of uncertainty we encounter in our project. Our research focus lies on the investigation of language elaboration processes in Middle Low German. We are particularly interested in diachronic constructional changes and constructionalizations involving and affecting all linguistic dimensions. For this, it is necessary to annotate our corpus with Part-of-Speech and constructional tags. Here, we are confronted with gradualness, gradience, and ambiguity as potential sources of uncertainty that complicate the annotation process. Furthermore, due to the historicity of the investigated language, we expect cases of incomplete knowledge and comparative fallacy from the annotators. For this reason, we develop an interface that captures all annotators’ doubts.
Keywords: historical languages; linguistic annotations; gradience and gradualness; ambiguity; incomplete knowledge

Towards a Multi-Stage Approach to Detect Privacy Breaches in Physician Reviews - Bäumer, Frederik Simon; Kersting, Joschka; Orlikowski, Matthias; Geierhos, Michaela (Proceedings of the Posters and Demos Track of the 14th International Conference on Semantic Systems co-located with the 14th International Conference on Semantic Systems (SEMANTiCS 2018))
Physician Review Websites allow users to evaluate their experiences with health services. As these evaluations are regularly contextualized with facts from users’ private lives, they often accidentally disclose personal information on the Web. This poses a serious threat to users’ privacy. In this paper, we report on early work in progress on “Text Broom”, a tool to detect privacy breaches in user-generated texts. For this purpose, we conceptualize a pipeline which combines methods of Natural Language Processing such as Named Entity Recognition, linguistic patterns and domain-specific Machine Learning approaches which have the potential to recognize privacy violations with wide coverage. A prototypical web application is openly accesible.
Keywords: Detection of Privacy Violations; Physician Reviews

Flexible Ambiguity Resolution and Incompleteness Detection in Requirements Descriptions via an Indicator-based Configuration of Text Analysis Pipelines - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 51st Hawaii International Conference on System Sciences)
Natural language software requirements descriptions enable end users to formulate their wishes and expectations for a future software product without much prior knowledge in requirements engineering. However, these descriptions are susceptible to linguistic inaccuracies such as ambiguities and incompleteness that can harm the development process. There is a number of software solutions that can detect deficits in requirements descriptions and partially solve them, but they are often hard to use and not suitable for end users. For this reason, we develop a software system that helps end-users to create unambiguous and complete requirements descriptions by combining existing expert tools and controlling them using automatic compensation strategies. In order to recognize the necessity of individual compensation methods in the descriptions, we have developed linguistic indicators, which we present in this paper. Based on these indicators, the whole text analysis pipeline is ad-hoc configured and thus adapted to the individual circumstances of a requirements description.
Keywords: Software Product Lines: Engineering; Services; and Management; Ambiguities; Incompleteness; Natural Language Processing; Software Requirements

Unschärfe bei der Interpretation natürlichsprachlicher Anforderungsbeschreibungen - Geierhos, Michaela (Unschärfe - Der Umgang mit fehlender Eindeutigkeit)
Präzision ist kein Zufall. Sie wird vom Menschen herbeigeführt, indem Übereinstimmung mit einem Standard oder einem akzeptierten Wert angestrebt wird oder die Reproduzierbarkeit von Experimenten möglichst hoch sein muss. Was aber tun, wenn Präzision mangels verfügbarer Informationen nicht hergestellt werden kann? Wie gehen Wissenschaft und Kunst dann mit dieser fehlenden Eindeutigkeit um? Die Autorinnen und Autoren dieses Sammelbandes beleuchten aus der Perspektive ihrer jeweiligen Fachdisziplin die Chancen bei der Berücksichtigung von Unschärfe(n) in ihrer Forschung und Kunst. Denn Unschärfe ist Realität.

How to Deal with Inaccurate Service Requirements? Insights in Our Current Approach and New Ideas - Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
The main idea in On-The-Fly Computing is to automatically compose existing software services according to the wishes of end-users. However, since user requirements are often ambiguous, vague and incomplete, the selection and composition of suitable software services is a challanging task. In this paper, we present our current approach to improve requirement descriptions before they are used for software composition. This procedure is fully automated, but also has limitations, for example, if necessary information is missing. In addition, and in response to the limitations, we provide insights into our above-mentioned current work that combines the existing optimization approach with a chatbot solution.

CORDULA: Software Requirements Extraction Utilizing Chatbot as Communication Interface - Friesen, Edwin; Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
Natural language requirement descriptions are often unstructured, contradictory and incomplete and are therefore challenging for automatic processing. Although many of these deficits can be compensated by means of Natural Language Processing, there still remain cases where interaction with end-users is necessary for clarification. In this paper, we present our idea of using chatbot technology to establish end-user communication in order to support the automatic compensation of some deficits in natural language requirement descriptions.

Back to Basics: Extracting Software Requirements with a Syntactic Approach - Caron, Matthew; Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
As our world grows in complexity, companies and employees alike need, more than ever before, solutions tailored to their exact needs. Since such tools cannot always be purchased off-the-shelf and need to be designed from the ground up, developers rely on software requirements. In this paper, we present our vision of a syntactic rule-based extraction tool for software requirements specification documents. In contrast to other methods, our tool will allow stakeholders to express their needs and wishes in unfiltered natural language, which we believe is essential for non-expert users.

Book review: Roger Sell (ed.) (2014). 'Dialogue as Literature.' Amsterdam: John Benjamins - Mildorf, Jarmila (Partial Answers)

Mündliches Erzählen / Alltagserzählungen - Mildorf, Jarmila (Erzählen)

Reading (Fictional) Dialogue: Text, Context, Cognition - Mildorf, Jarmila